2021
DOI: 10.4081/aiua.2021.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Detection limits of significant prostate cancer using multiparametric MR and digital rectal examination in men with low serum PSA: Up-date of the Italian Society of Integrated Diagnostic in Urology

Abstract: Reasons why significant prostate cancer is still missed in early stage were investigated at the 22nd National SIEUN (Italian Society of integrated diagnostic in Urology, Andrology, Nephrology) congress took place from 30th November to 1st December 2020, in virtual modality. Even if multiparametric magnetic resonance (MR) has been introduced in the clinical practice several, limitations are emerging in patient with regular digital rectal examination (DRE) and serum prostate specific antigen (PSA) levels approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
(52 reference statements)
0
8
1
Order By: Relevance
“…Studies have shown that the ORs and 95%CI of poor histological prognosis of prostate were 2.21 (1.30-3.76) and 1.58 (0.90-2.76) in men over 80 years old compared with those under 70 years old, respectively (20). Although this study did not prove a positive correlation between prostate volume and the occurrence of csPCa, several studies have confirmed that PSAD (PSA value/gland volume) was independently correlated to csPCa even in patients with serum PSA slightly above limits or even within normal limits, which was observed in every clinical scenario early diagnosis, repeat biopsy, and active surveillance (21). For example, Roscigno et al found that higher PSAD was associated with higher risk of reclassification at confirmatory or follow-up biopsy using 0.20 as cutoff (22).…”
Section: Clinical-radiomic Modelcontrasting
confidence: 66%
“…Studies have shown that the ORs and 95%CI of poor histological prognosis of prostate were 2.21 (1.30-3.76) and 1.58 (0.90-2.76) in men over 80 years old compared with those under 70 years old, respectively (20). Although this study did not prove a positive correlation between prostate volume and the occurrence of csPCa, several studies have confirmed that PSAD (PSA value/gland volume) was independently correlated to csPCa even in patients with serum PSA slightly above limits or even within normal limits, which was observed in every clinical scenario early diagnosis, repeat biopsy, and active surveillance (21). For example, Roscigno et al found that higher PSAD was associated with higher risk of reclassification at confirmatory or follow-up biopsy using 0.20 as cutoff (22).…”
Section: Clinical-radiomic Modelcontrasting
confidence: 66%
“…This reallocation could lead to further investigations for the patient, with subsequently diagnostic pathway modifications and additional costs. Nevertheless, our hypothesis is validated by the recent changes of PI-RADS system, where DCE's role is to distinguish PI-RADS 3 versus PI-RADS 4 lesions, in case of T2 -DWI/ADC mismatch (25)(26)(27)(28)(29)(30)(31)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 61%
“…Diagnosis and management of Pca can be implemented by multivariate stratification based on patient risk (PSA, DRE, age), associated with BP-MRI (scenario 2). Some trials show that stratifying patients can be a winning strategy to maximize benefits and reduce costs for both diagnosis and therapy (14,(29)(30)(31)(32)(33)(34)(35)(36)(37). An important implication of BP-MRI, however, regards the PIRADS assessment categories, as already well explained in PIRADS guidelines v2.1 (2).…”
Section: Discussionmentioning
confidence: 99%
“…Downsizing tumor can be related to MRI limitations. That could be also called “MRI undersizing”: tumor located at margins of the MR lesion are not visible at MRI ( 39 ). That is related to tumor heterogeneity in terms of not-round tumor shape and volume other than histologic sub-type and grading ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…That could be also called “MRI undersizing”: tumor located at margins of the MR lesion are not visible at MRI ( 39 ). That is related to tumor heterogeneity in terms of not-round tumor shape and volume other than histologic sub-type and grading ( 39 ). Combining these variables, we can imagine how many possible variations could influence final tumor extension and exact location of the most aggressive tumor.…”
Section: Discussionmentioning
confidence: 99%